Technician Scheduling Design Application On PT Orela Shipyard Surabaya - Dewa, Bagus Anggoro Putra; Sudarmaningtyas, Pantjawati; Mujayana, Marya (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
PT Orela Shipyard is a company that works in industrial ship makers. The problem that has been occured all this time is a few site often left unguarded by the technician so the ship repair service can be said not to good. This is caused by scheduling process that are not optimized. Scheduling process that has been don is not well organized, each technician is scheduled from one site to the other directly without using method that optimized it.Application that has been build can be use to scheduling the technician according to the need of the user. Scheduling calculation Round Robin Tournament method and the process of making the application can be done with a few step that is communication, planning, modelling and construction.The result based from the application trials, the application has been made can solve the problem of PT Orela Shipyard in scheduling of the technician with producing schedule according to the need of each site so there are no more empty site or being left unguarded all day long. Technician scheduling application can handle the data that need scheduling, technician scheduling process and technician presence, so it can produce technician data, site data and detail presence report. This is sustained by the result from application trials by using black box testing that focused on user input function with the system showing perfect score of 100% shows this application is can be used.